Diseño y construcción de un prototipo de brazo robótico industrial a escala. - Trelles Jaramillo, Carlos Alberto (2021)
In the present work, a prototype of industrial robotic arm of 6 degrees of freedom was designed and built whose structure is of carbon fiber printed in 3D, being validated with a maximum load of 0,5 kg. The conceptual design of the arm was inspired by an anthropomorphic robot model defining six main joints (base, shoulder, arm, elbow, forearm and wrist), achieving a wide working area to perform pick and place operations, welding, palletizing, painting, milling, among others. In the detailed design, kinematic and dynamic simulations were performed in the Adams View application, facilitating the obtaining of operational characteristics, forces and power requirements. For the power transmission components: shafts, bearings, transmission by synchronism belts and gears the different design theories of machine elements were used. The control system is based on a mini driver for Monster VNH2SP30 30A Dual engine commanded by Arduino and programmed in Arduino IDE. Finally, the construction and design of the prototype was validated and subjected to tests of movement, precision and resistance. In the tests of movement the speed was measured in r.p.m with which it can work each of the joints, in those of precision the angles (º) were obtained the maximum load in kg that each part of the robotic arm can withstand. A prototype was obtained at scale, industrial and functional, which meets all the expectations raised in the project. Keywords: robotic arm prototype, design, robotics.